Assessing the Impact of Training Intervention to Improve Respectful Maternity Care among Health Workers: A Quasi-Experimental Study - Beig, Mirza Adil; Kumar Sharma, Rajeev; Gauniyal, Mansi (Journal of Neonatal Surgery, 2025)
Background: Respectful Maternity Care (RMC) is a fundamental right for all childbearing women and a crucial component of high-quality maternal health services. Despite national efforts like the LaQshya initiative, there are still significant gaps in implementation. These gaps are largely due to insufficient training and lack of awareness among healthcare providers. Objectives: This study aims to evaluate the impact of a structured training program on enhancing healthcare workers' knowledge, attitudes, and self-perceived behaviors related to Respectful Maternity Care. Materials and Methods: A quasi-experimental study was conducted among 50 health workers involved in intrapartum care at two public sector hospitals in Kushinagar district, Uttar Pradesh. Participants underwent baseline assessment, followed by a structured one-day RMC training. Posttest evaluation was also conducted. Data was collected through a validated questionnaire comprising 20 knowledge-based multiple-choice items, 10 scenario-based attitude items, and 5 Likert-scale items on self-perceived RMC behavior. Statistical analysis involved paired t-tests with a significance level set at p<0.05. Results: The average knowledge score saw a significant increase from 58.4 ±10.3 to 81.2 ±7.6 after the training (p<0.001). Specific areas of improvement included informed consent practices (from 49.1% to 82.5%), communication skills (from 55.8% to 80.2%), privacy maintenance (from 61.4% to 83.1%), and abuse recognition (from 67.3% to 79.6%). Participants also reported greater empathy, better communication, and a stronger focus on informed consent in their daily routines. Conclusion: Structured training programs substantially improve the knowledge and attitudes of maternity care providers regarding Respectful Maternity Care. For lasting improvements, it is crucial to integrate RMC modules into regular in-service training and support them with institutional policies.